1999
DOI: 10.1111/0019-8676.00141
|View full text |Cite
|
Sign up to set email alerts
|

Industrialization, Female Labor Force Participation, and the Modern Division of Labor by Sex

Abstract: We examine the effect of industrialization on female labor force participation for 62 countries. Two hypotheses are tested: the emancipation hypothesis and the U-shaped hypothesis. Our results support the U-shaped hypothesis insofar as shifts in the distribution of occupations in early industrialization decrease female labor force participation by removing women from agriculture while excluding them from occupations in manufacturing and management. We further suggest that different paths to industrialization m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
0
7
0
5
Order By: Relevance
“…In examining the intricate concept of women's empowerment, some measures that have been studied are the relationship between development and female labor force participation rate (FLFPR), also known as the U curve hypothesis, (Boserup 1970;Durand 1975;Goldin 1994;Galor & Weil 1996;Rau and Wazienski 1999;Mammen & Paxson 2000;Fuwa et al, 2006;Lincove, 2008), fertility (Galor & Weil 1996;Angeles et al 2005), educational attainment (Lincove 2008;Nuss & Majka 1985;Goldin 1994) , decision making ability (Amin & Lloyd 2002;Fletschner 2008), and the population sex ratio. (Sen 1992) The literature on the enormous opportunities ICTs can provide for women's empowerment is vibrant and wide ranging.…”
Section: Women Empowerment and Ictmentioning
confidence: 99%
“…In examining the intricate concept of women's empowerment, some measures that have been studied are the relationship between development and female labor force participation rate (FLFPR), also known as the U curve hypothesis, (Boserup 1970;Durand 1975;Goldin 1994;Galor & Weil 1996;Rau and Wazienski 1999;Mammen & Paxson 2000;Fuwa et al, 2006;Lincove, 2008), fertility (Galor & Weil 1996;Angeles et al 2005), educational attainment (Lincove 2008;Nuss & Majka 1985;Goldin 1994) , decision making ability (Amin & Lloyd 2002;Fletschner 2008), and the population sex ratio. (Sen 1992) The literature on the enormous opportunities ICTs can provide for women's empowerment is vibrant and wide ranging.…”
Section: Women Empowerment and Ictmentioning
confidence: 99%
“…In fact, most studies on the effect of modernization on women's LMP found an nonlinear relationship, with decreasing LMP in the earlier phase of modernization and increasing LMP in the later phase (e.g. Sinha, 1967;Durand, 1975;Tilly & Scott, 1978;Pampel & Tanaka, 1986;Psacharopoulos & Tzannatos, 1989;Rau & Wazienski, 1999; Lincove, forthcoming). This U-curve relationship has been explained by the different processes taking place in the early and late phases of modernization.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…At the same time, the newly emerging industrial jobs offered no real alternative to them, as their caring duties bounded them to their homes and most new jobs required physical strength and therefore were not considered to be compatible with women's roles at home. Women's employment chances were also reduced by their lower levels of education and training and by sex discrimination at the labor market (Scott & Tilly, 1975;Boserup, 1977, Pampel & Tanaka, 1986Rau & Wazienski, 1999). The upward part of the U-curve has been related to a number of factors and processes taking place in advanced industrial societies that promote the employment of women.…”
mentioning
confidence: 99%
“…Some of this work also suggests a curvilinear relationship, where gender inequality first increases and then decreases with development much along the lines of evidence of the 'feminization-U', where women's labour force participation first increases and then decreases with industrialization (Rau and Wazienski, 1999;Forsythe et al, 2000). Others argue that the impact of growth and structural change, including globalization, may have negative effects on women's well-being and gender equality (Seguino, 2000a(Seguino, , 2007Berik, 2008).…”
Section: Gender and Growthmentioning
confidence: 92%